PENGARUH LITERASI DAN PENGALAMAN KEUANGAN TERHADAP PENGELOLAAN KEUANGAN MELALUI NIAT BERPERILAKU PADA PENGRAJIN KASUR BUSA KECAMATAN PAKISAJI KABUPATEN MALANG - Fawwaz, Muhammad Iqbal; Pratikto, Heri (Transpublika Publisher, 2023)
In developing a business, financial management of MSMEs plays an important role. This study aims to examine the effect of financial literacy and experience on the financial management of foam mattress craftsmen, as well as to examine whether behavioral intention is a mediating variable between financial literacy and experience with financial management. The survey was conducted on foam mattress craftsmen using total sampling technique, and the data were analyzed using Path Analysis. The results showed a significant positive influence between financial experience and financial management behavior. In addition, this study proves that financial literacy has an indirect effect on financial management through behavioral intentions. The managerial implications of this study emphasize the importance of having good financial experience in improving financial management. In addition, this study provides new insights that individuals with high financial literacy also need to have good Financial behavioral intentions to manage their business finances more carefully.